Clinico- etiological profile of acute poisoning and intoxication in children in western Nepal - Sah, Love K.; Mahat, Munu; Pareek, Prince; Pokhrel, Ram P.; Garegrat, Reema (International Journal of Contemporary Pediatrics, 2021)
Background: Pediatric poisoning is a common emergency. The present study was done to assess the incidence, clinico-etiological profile of acute poisoning and intoxication in children. Methods: This study was conducted in the Department of Pediatrics, Lumbini Medical College and Teaching Hospital, Nepal in which children aged less than 18 years, with history of consumption of poison accompanied or unaccompanied by container or poison or with doubtful history of consumption of poison but with definite signs and symptoms of acute poisoning we included. We also included children with history of bites by poisonous creatures like snakes, scorpions, bees and insects or with doubtful history of bites due to poisonous creatures but with definite acute onset of signs and symptoms locally or systemically. Results: In the present study, during the study duration, 68 children were included. The most common age group of included children was 1 to 5 years (59%). Accidental poisoning was reported in 93% of the cases, while the rest had suicidal poisonings. The most common type of poison used were different types of pesticides (46%). We observed that vomiting was the most common clinical presentation (79%). In our study sample, arrival of 46% of the children was delayed by 30 minutes to 2 hours. Majority of the patients arrived in the afternoon to the hospital (51%). Conclusions: The findings of the present study would enable emergency physicians to identify clinical features of common poisonings among children, which would enable manage the cases better.